A Rare Case of Streptococcal Toxic Shock Syndrome - Janani Arul; Poornima Kumar; Lalitha Krishnan (JCDR Research and Publications Pvt. Ltd., 2020)
This article reports a case of 16-day-old male baby with features of cellulitis in the diaper area and shock. Blood culture report of baby and high vaginal swab of mother grew Group A Streptococcus (GAS) and the neonate was diagnosed to have Streptococcal toxic shock syndrome. Hence, a case of Streptococcal toxic shock syndrome must be identified as early as possible, which is a rare and life threatening condition in a newborn.